THE ROLE OF TAX AUTHORITIES IN MONITORING FOREIGN TRADE OPERATIONS IN THE DEVELOPMENT OF COMPETITION - Khusanov Fakhriddin (Scholars Digest Publishing, 2023)
This article describes the stages of monitoring foreign trade operations to ensure the implementation of foreign trade contracts concluded by businesses through a single electronic information system of foreign trade operations and the exchange of information between businesses, customs and tax authorities, Central and commercial banks in the context of competition. Also, scientific proposals were made to further improve the work of tax authorities in monitoring foreign trade operations in the development of competition.
Keywords: competition, foreign trade, commercial banks, budget organizations, recipients of budget funds, treasury departments, commodities, import contracts